An Analysis of Ecranisation Process of Intrinsic Elements in Novel to Film “Five Feet Apart” by Rachael Lippincott - Rizki Tania Putri; Fauziah Khairani Lubis; Elisa Betty Manullang (Universitas Negeri Medan, 2021)
This study aims to determine the changes experienced by intrinsic elements found in the novel